Text Mining: Absolute Advantage Research at Scopus - Mubarak, Fadhlul; Aslanargun, Atilla; Sundara, Vinny Yuliani; Nurniswah, Nurniswah (ESTIMASI: Journal of Statistics and Its Application, 2024)
This study aims to collect scopus indexed articles with the keyword absolute advantage in 2020, 2021, and 2022 (until July 15, 2022). In addition, we analyzed the text mining of several abstracts from these articles using the R software. we used 75 articles from top 3 journals that have most publications based on the keyword including the Journal of Cleaner Production, the Journal of Chemical Engineering, and the Journal of Applied Soft Computing. Based on data mining analysis, the word-cloud of each abstract automatically appears based on the frequency of each word that appears in the abstract.